Practitioners' perceptions of an innovative school system in a developing country: A qualitative analysis - Harvey, Claudia (1981)
This analysis of the senior secondary comprehensive school sector of Trinidad and Tobago was undertaken in three phases. The first was to understand the overall setting of secondary education in the country. The second was to identify and classify issues which fell into five basic categories: students, personnel, curriculum and examinations, perceived goals and achievement, and external factors. The third and interpretive phase sought to locate the study in the wider contexts of methodology, theory, and practice
Keywords: Senior secondary schools